Effects of hydraulic retention time on anaerobic digestion of domestic wastewater at low loading rates - Tan, Y.Y.J.; Ramachandran, K.B.; Hashim, M.A. (2008)
The hydraulic retention time has been identified as the key operating parameter that affects the performance of the UASB reactor. For low-strength wastewaters such as the domestic wastewater, it is the limiting design parameter. Hydraulic retention times that are too long or too short would adversely affect the performance of the UASB reactor. The highly fluctuating flow rates of domestic wasterwater, which corresponds to fluctuating hydrualic retention times, have been cited as one of the inherent difficulties for application of the UASB reactor in domestic wastewater treatment. The generally low organiz loading of domestic wastewaters further compounds the challenges of treatment by anaerobic digestion. This paper reports the effect of highly fluctuating hydraulic retention times on the performance of a UASB reactor in treating domestic wastewater at low loading rates with the aim of gaining a better understanding of its application. From the result obtained, conclusions derived are that the hydraulic retention time does not affect the effluent COD: fluctuating hydraulic retention times within the range in this study did not adversely affect the performance of the UASB reactor; longer hydraulic retention times give better COD degradation rates; and generally, for very similar volumetric loading rates, COD removal efficiency is lower as shorter hydraulic retention times.